2022
DOI: 10.1155/2022/3150099
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Impact of Cultural Creative Product Design for Sport Events on the Residents’ Fitness

Abstract: Cultural and creative product design of sports events is an important part of sports industry, which can improve the economic benefits of sports industry. Based on this background, this paper puts forward a regression analysis method to deeply analyze the design of cultural and creative products in sports events, aiming at driving the healthy development of residents and improving their health levels. First of all, 620 residents were randomly divided into a control group and an observation group to compare nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Regarding the cultural and creative industries, the eastern region is the best developed, while the western region is the worst (Li et al, 2022). Because this figure covers the sum of the added value of the regional cultural and creative industries, which is not so objective, it is worth taking both the sum to Figure 2, which is more objective and transparent about the development of the cultural and creative industries (N. Liu & Zhang, 2022). At the same time, due to special reasons in 2020, taking the data of 2019 as an example, the top five provinces and cities in terms of added value of cultural and creative industries are Guangdong, Jiangsu, Zhejiang, Beijing, and Shandong, with Guangdong being particularly prominent, with an added value of 622.7 billion yuan, which is more than 100 times that of Qinghai, which has the most negligible added value of cultural and creative industries.…”
Section: The Scale Of Cultural and Creative Industries Continues To E...mentioning
confidence: 99%
“…Regarding the cultural and creative industries, the eastern region is the best developed, while the western region is the worst (Li et al, 2022). Because this figure covers the sum of the added value of the regional cultural and creative industries, which is not so objective, it is worth taking both the sum to Figure 2, which is more objective and transparent about the development of the cultural and creative industries (N. Liu & Zhang, 2022). At the same time, due to special reasons in 2020, taking the data of 2019 as an example, the top five provinces and cities in terms of added value of cultural and creative industries are Guangdong, Jiangsu, Zhejiang, Beijing, and Shandong, with Guangdong being particularly prominent, with an added value of 622.7 billion yuan, which is more than 100 times that of Qinghai, which has the most negligible added value of cultural and creative industries.…”
Section: The Scale Of Cultural and Creative Industries Continues To E...mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%